Mismatch repair deficiency in early‐onset duodenal, ampullary, and pancreatic carcinomas is a strong indicator for a hereditary defect. (6th December 2021) - Kryklyva, Valentyna; Brosens, Lodewijk AA; Marijnissen‐van Zanten, Monica AJ; Ligtenberg, Marjolijn JL; Nagtegaal, Iris D
Abstract: Mismatch repair deficiency (dMMR) is a hallmark of Lynch syndrome (LS), but its prevalence in early‐onset (diagnosed under the age of 50 years) duodenal, ampullary, and pancreatic carcinomas (DC, AC, and PC, respectively) is largely unknown. We explored the prevalence of dMMR and the underlying molecular mechanisms in a retrospectively collected cohort of 90 early‐onset carcinomas of duodenal, ampullary, and pancreatic origin. dMMR was most prevalent in early‐onset DCs (47.8%); more than half of those were associated with hereditary cancer syndromes (LS or constitutional mismatch repair deficiency syndrome). All dMMR AC and PC were due to LS. Concordance of dMMR with underlying hereditary condition warrants ubiquitous dMMR testing in all early‐onset DC, AC, and PC.